1999
DOI: 10.1111/j.1572-0241.1999.01013.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Infection in Patients With Inflammatory Bowel Disease

Abstract: Cytomegalovirus infection may play a role in the natural history of refractory inflammatory bowel disease and in some of its complications. The clearance of cytomegalovirus in colonic mucosa may lead some of these patients to remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 13 publications
1
92
0
5
Order By: Relevance
“…Cytomegalovirus (CMV) reactivation is known as an important exacerbating factor (20)(21)(22). However, the clinical significance of CMV reactivation remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) reactivation is known as an important exacerbating factor (20)(21)(22). However, the clinical significance of CMV reactivation remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…These factors included female gender, pancolonic disease with active inflammation at histology, and azathioprine treatment. Using antigenemia, Wada [15] reported a prevalence of 34%, while Vega [16] reported a result of 3% in a retrospective study that used HE and ICH results. Severe steroid-resistant colitis: Cottone et al [17] showed that the prevalence of CMV, studied using HE and ICH and antigenemia, was 36%.…”
Section: Patient Selection Methodsmentioning
confidence: 99%
“…En la CU, la reactivación local de CMV se manifiesta habitualmente por crisis graves refractarias a corticoides 31,32,[34][35][36][37] . Estudios de cohorte informan una prevalencia de reactivación viral que varía entre 4,6 y 25% [38][39][40][41][42][43][44] .…”
Section: Rol De Citomegalovirus En Crisis Grave De Enfermedad Inflamaunclassified
“…En pacientes con estudio positivo, la medición de carga viral en sangre o antigenemia pueden ayudar a guiar la terapia, aunque los valores de corte no son claros. La terapia antiviral sugerida es ganciclovir endovenoso por 14 días, cuya tasa de respuesta varía entre 60 y 86%; sin embargo, la evidencia está limitada a estudios observacionales de tipo cohorte 35,45,49,[51][52][53] . La respuesta se observa al quinto o séptimo día de tratamiento.…”
Section: Rol De Citomegalovirus En Crisis Grave De Enfermedad Inflamaunclassified